An analytical model for flexural vibration of composite beams with shear slip based on third order deformation kinematics. (April 2022) - Wen, Jie; Hamid Sheikh, Abdul; Alhaz Uddin, Md.; Uy, Brian
Abstract: In this paper, an analytical solution is derived for accurately predicting the free and forced vibration responses due to time varying as well as moving loads of two layered composite beams which consist of two different materials. For this purpose, the third order deformation kinematics is used in the proposed model, and it allows to take a parabolic (third order) variation of the longitudinal displacement along the beam depth for the two material layers. The partial shear interaction between the two material layers produced by the deformability of shear connectors joining these layers in the form of shear slip at their interface is modelled using distributed shear springs along the beam length. Hamilton's principle is applied to derive the governing equations of the dynamic system which are solved analytically using a Navier type solution technique. Moreover, a two-dimensional (2D) finite element model is built up in ABAQUS for the validation of the proposed analytical model. Some parametric studies are conducted to investigate the effect of shear deformation on the forced vibration response of a two-layered composite beam partial with different shear stiffness, span-to-depth ratio and elastic-to-shear modulus ratio.